Formulation of sunscreen cream from seaweed (Turbinaria sp.) and Kaempferia galangal - Jumsurizal Jumsurizal; Raja Marwita Sari Putri; Aidil Fadli Ilhamdy; Ginanjar Pratama; Riska Chintami Aulia (Jurnal Perikanan dan Kelautan, 2019)
Sunscreen cream products are usually derived from ingredients that contain an anti-UV component. Kaempferia galanga and Turbinaria sp. as long as it was known to have a good anti-UV light. However, research on the formulation of sunscreen creams from the two ingredients has never been done, so the need for research from both materials. The objective of this study was to get the best formulation of sunscreen cream from seaweed (Turbinaria sp.) and K. galanga. The treatments used in this study were the ratio between seaweed Turbinaria sp. and K. galanga in a ratio of 1: 1 (Cream A), 1: 2 (Cream B), 2: 1 (Cream C), and control (Cream D). The overall organoleptic value of aroma was not significantly different, whereas the best value for color and texture was found in cream B with an organoleptic value of color 3.27 and texture 3.2. All treatments were homogeneous and had an O/W emulsion type. pH and viscosity values in all treatments were by the applicable cosmetic cream requirements. The highest SPF value was found in cream B with a value of 18.04 ± 4.72. That makes cream B was the best treatment in this study